La Real Academia Sueca de Ciencias ha decidido entregar el Premio en hana Economía del Banco de Suecia en memoria de Alfred Nobel a los profesores James Heckman y Daniel Mcfadden por sus contribuciones a la Microeconometría - Heckman, James (2000)
Micro-econometric research deals with the empirical analysis of the economic behavior of individual agents and households, in relation to their decisions about the job offer, consumption, migration, occupational category they want to occupy, etc. Micro-econometric methods are equally relevant in studies of business behavior, as it relates to their production or employment decisions of the work factor, for example. In recent decades, significant advances in empirical micro-econometric research have been achieved thanks to innovations in micro-econometric methods and the increased availability of new kinds of data. The raw material in micro econometric research is data at the micro level, where individual agents, households or companies are the units of observation. Information at the micro level appears in the form of cross-sectional data, and increasingly in the form of panel data.